2016
DOI: 10.1002/jat.3279
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ionic silver to genotoxic potential of nanosilver in human liver HepG2 and colon Caco2 cells evaluated by the cytokinesis‐block micronucleus assay

Abstract: Extensive human exposure to food-and cosmetics-related consumer products containing nanosilver is of public concern because of the lack of information about their safety. Genotoxicity is an important endpoint for the safety and health hazard assessment of regulated products including nanomaterials. The in vitro cytokinesis-block micronucleus (CBMN) assay is a very useful test for predictive genotoxicity testing. Recently, we have reported the genotoxicity of 20 nm nanosilver in human liver HepG2 and colon Caco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
(159 reference statements)
2
21
0
Order By: Relevance
“…The comet assay and the cytokinesis‐block micronucleus assay showed that both AgNPs and PVP‐AgNPs could induce DNA and chromosome damage in HepG2 cells. Additionally, Sahu et al found that in HepG2 cells and Caco cells, the frequency of micronucleus binuclear cells induced by nanosilver at the concentration range of 0.5‐15 μg/mL increased in a concentration‐ and time‐dependent manner (Sahu, Roy, Zheng, & Ihrie, ). Papageorgiou et al () confirmed that the mitotic index of MCF‐7 cells and HepG2 cells decreased with the increase of nanosilver concentration, they also observed different types of chromosome aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…The comet assay and the cytokinesis‐block micronucleus assay showed that both AgNPs and PVP‐AgNPs could induce DNA and chromosome damage in HepG2 cells. Additionally, Sahu et al found that in HepG2 cells and Caco cells, the frequency of micronucleus binuclear cells induced by nanosilver at the concentration range of 0.5‐15 μg/mL increased in a concentration‐ and time‐dependent manner (Sahu, Roy, Zheng, & Ihrie, ). Papageorgiou et al () confirmed that the mitotic index of MCF‐7 cells and HepG2 cells decreased with the increase of nanosilver concentration, they also observed different types of chromosome aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…OECD TG 487 [64] was followed in studies carried out by five authors: Sahu et al [73], Ivask et al [74], Guo et al [72], Sahu et al [75] and Sahu et al [76]. According to OECD TG 487 [64], human peripheral blood lymphocytes and some rodent cell lines such as CHO, V79 and L5178Y or human cell lines such as TK6 are considered suitable for performing this assay; however, other cell lines such as HT29, Caco-2, HepG2 and A549, which have been used in several studies, have not been extensively validated by OECD TG 487 [64].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Tests on different human cell line models showed tissue-dependent sensitivity and the importance for applied doses potentially used in anticancer therapies of NPs. The same research group, working again with HepG2 and Caco-2 cells, discussed the genotoxic potential of AgNPs as a result of chromosome damage during mitosis, where chromosomal abnormalities occurred as seen by micronucleus formation (Mn assay) [43]. The nanosilver genotoxicity resulted in viability reduction in a dosedependent manner and was explained by cytokinesis blockade [43], which could be a result of abnormal formation of histone H2A, that disrupts cellular division and proper chromatin (chromosome) formation [44].…”
Section: Antiproliferative Activitymentioning
confidence: 99%